LECTURER QUALITY EMPOWERMENT STRATEGY IN REALIZING NATIONAL EDUCATION OBJECTIVES - Asmawi, Muhammad Rosul (Perspektif : Jurnal Ilmu Administrasi, 2019)
This study aims to find out the position and role of lecturers in carrying out the task of implementing the national education system and realizing the goals of national education. Lecturers are one of the determinants of the quality of education. The success of the implementation of higher education is largely determined by the readiness of the lecturer in preparing their students through teaching and learning activities or the learning process. The strategic position of lecturers to improve the quality of educational outcomes is strongly influenced by professional abilities in teaching and their level of welfare. To realize this; then the strategy of empowering lecturers is needed in order to realize professionalism that can be accounted for. The empowerment strategy implemented will be able to raise the dignity and level, improve the quality of learning, improve the quality of national education and provide quality services. Empowerment of lecturers is intended to create a work atmosphere or climate that leads to the development of potential, empowerment, and protection.